Disaster Regime Character: A Study of Disaster Risk Reduction at Merapi Volcano Eruption in Sleman District - Nurlia Dian Paramita (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2012)
This research analyses how the existence of the character occurred in one of disaster management phases which is an emergency response. In addition, it aims to discuss and see the relationship between authority institutions in the disaster management which are Kesbanglinmas & PB Kab. Sleman, Muhammadiyah Disaster Management Centre (MDMC), and Merapi Circle Information Network (JALIN MERAPI). This research uses qualitative method. The data about the policy and survivor handling are got through interviews with representatives from Pakem, Turi, and Cangkringan. They are head of sub districts, head of villages, and head of country-sides. The findings of this research show that the disaster regime character is fatalist-individualist and the authority relation is substitution (acts as a substitute). Therefore, humanity-based point of view is important to see the risk. It will empower the capacity of government institutions. The last, involving civil society (CSO) is also significant to streamline the role of disaster management regime guide. Therefore, the synergy between government and CSO will easily be achieved to implement Community-Based Disaster Risk Management (CBDRM). CSO is the government’s partner to reduce disaster.